Proceedings of 11th Symposium on Nuclei in the Cosmos — PoS(NIC XI) 2011
DOI: 10.22323/1.100.0212
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of 26Si for application to nova gamma-ray emission.

Abstract: 26 Al was the first cosmic radioactivity ever detected in the galaxy. Its nucleosynthesis in novae outbursts is still uncertain mainly due to the lack of nuclear information concerning the 25 Al(p,γ) 26 Si reaction. We report here on a neutron-gamma coincidence measurement of the 24 Mg( 3 He,nγ) 26 Si reaction performed at the Orsay TANDEM facility aiming at the spectroscopic study of astrophysically important 26 Si states. A new level in the Gamow peak is observed at E X = 5.888 MeV and the gamma-ray decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…An additional open question has been recently highlighted by studies of the 24 Mg( 3 He, nγ) 26 Si reaction [268,269,271]. Population of a new level at 5890 keV has been observed and conclusively identified as a 0 + state [269].…”
Section: Neutron-induced Destruction Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional open question has been recently highlighted by studies of the 24 Mg( 3 He, nγ) 26 Si reaction [268,269,271]. Population of a new level at 5890 keV has been observed and conclusively identified as a 0 + state [269].…”
Section: Neutron-induced Destruction Reactionsmentioning
confidence: 99%
“…Note that in [258], the 5928 keV state was labeled as 5916 keV as a result of the uncertain calibration of lower-lying levels [273], and it would be worthwhile to revisit the data from that measurement in light of the more precise energy measurements currently available. Another question is why is the 5890 keV 0 + state so readily observable in the 24 Mg( 3 He, nγ) 26 Si studies [266,268,269,271], but no neutrons were observed populating the state in the 24 Mg( 3 He, n) 26 Si measurement [261], which seemingly had the resolution to observe it? Finally, the question as to whether we are seeing too many 0 + levels and the assertion in [263] of a missing 1 − level clearly strains our ability to claim complete knowledge of the relevant 26 Si level structure.…”
Section: Neutron-induced Destruction Reactionsmentioning
confidence: 99%
“…As mentioned earlier, a potential new level at 5888(2) keV was recently reported in a study of the 24 Mg( 3 He, nγ) 26 Si reaction by de Séréville et al [36]. Its excitation energy was re-constructed from the observation of coincident γ-ray transitions of 1749(2), 3102(2) and 4091(2) keV to the bound 2 + states at 4139, 2785 and 1797 keV, respectively.…”
Section: Results and Conclusionmentioning
confidence: 81%
“…Furthermore, Bell et al [11] 26 Si in which neutrons were detected in coincidence with decay γ-rays [36], a potentially important new state was found at 5888 keV via its decay cascade, which was not observed in either Ref. [20] or Ref.…”
Section: Introductionmentioning
confidence: 99%